Health consequences of obesity. Issue 9 (22nd August 2003) - Reilly, J J; Methven, E; McDowell, Z C; Hacking, B; Alexander, D; Stewart, L; Kelnar, C J H
Abstract : The recent epidemic of childhood obesity 1 has raised concern because of the possible clinical and public health consequences. 2, 3 However, there remains a widespread perception among health professionals that childhood obesity is a largely cosmetic problem, with minor clinical effects. No systematic review has yet focused on the diverse array of possible consequences of childhood obesity, though older non-systematic reviews are available. 4, 5 In addition, no review to date has considered the vast body of evidence on the health impact of childhood obesity which has been published recently. The aim of the present review was therefore to provide a critically appraised, evidence based, summary of the consequences of childhood obesity in the short term (for the child) and longer term (in adulthood).